1997
DOI: 10.1038/sj.cdd.4400231
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cyclin A-dependent kinases associated with WAF1 degradation during radiation-induced apoptosis

Abstract: We describe here the further characterisation of the radiation response of a pair of isogenic Burkitt's lymphoma cell lines which differ significantly in their susceptibility to radiation-induced apoptosis. In both cases a marked inhibition of cyclin A-dependent kinase activity was observed at 4 h post-irradiation which recovered to normal levels in the susceptible line by 12 h but remained inhibited in the resistant cell line. Under these conditions the cellular abundance of p58 cyclinA and p33 cdk2 did not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The cdks in turn are positively regulated by association with cyclins and are required for cell‐cycle progression (Norbury and Nurse, 1992; Morgan, 1995; Elledge et al ., 1996). Several reports have shown the activation of various Cdks to correlate with apoptosis (Meikrantz et al ., 1994; Shi et al ., 1994; Li et al ., 1995; Wei et al ., 1997; Zhang et al ., 1997; Levkau et al ., 1998). It has been shown that dominant negative alleles of Cdk2 can alleviate tumour necrosis factor‐α (TNFα)‐ and staurosporine‐induced apoptosis in HeLa cells (Meikrantz and Schlegel, 1996) and more recently, apoptosis induced by growth factor withdrawal from human umbilical vein endothelial cells (Levkau et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cdks in turn are positively regulated by association with cyclins and are required for cell‐cycle progression (Norbury and Nurse, 1992; Morgan, 1995; Elledge et al ., 1996). Several reports have shown the activation of various Cdks to correlate with apoptosis (Meikrantz et al ., 1994; Shi et al ., 1994; Li et al ., 1995; Wei et al ., 1997; Zhang et al ., 1997; Levkau et al ., 1998). It has been shown that dominant negative alleles of Cdk2 can alleviate tumour necrosis factor‐α (TNFα)‐ and staurosporine‐induced apoptosis in HeLa cells (Meikrantz and Schlegel, 1996) and more recently, apoptosis induced by growth factor withdrawal from human umbilical vein endothelial cells (Levkau et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Independent single-cell derived BaF3 clones with similar expression levels of the transfected Cdk2 protein behaved similarly to the clone shown (data not shown). Wei et al, 1997;Zhang et al, 1997;Levkau et al, 1998). It has been shown that dominant negative alleles of Cdk2 can alleviate tumour necrosis factor-α (TNFα)-and staurosporine-induced apoptosis in HeLa cells (Meikrantz and Schlegel, 1996) and more recently, apoptosis induced by growth factor withdrawal from human umbilical vein endothelial cells (Levkau et al, 1998).…”
Section: Introductionmentioning
confidence: 99%